Communication model of mosque youth lifestyle in religious life - Saka Mahardika Oktav N.; Juhadi; Hamdan Tri Atmaja; Nugroho Trisnu Brata (Program Pascasarjana Universitas Negeri Yogyakarta, 2025)
The youth community of Muhammadiyah mosques, Nahdatul Ulama (NU), Tabligh and the Indonesian Islamic Da'wah Institute (LDII) have differences in carrying out worship and lifestyle behaviors. This research has three main objectives: first, to describe the religious practices of the four mosque youth communities; second, to examine the lifestyle through the perspective of Islamic identity communication; and third, to formulate a model of lifestyle communication in the context of different religions between these communities. The approach of this research is qualitative with a phenomenological framework. The informants involved came from four mosque youth groups that were the object of the study. The results of the study show, first, that the differences in religious lifestyles among the four Muslim youth communities triggered friction between groups. Second, there are variations in lifestyles, ways of dressing or fashion, consumption patterns, and communication patterns have the potential for conflict leading to conflict. Third, this study succeeded in identifying two types of communication models: formal communication that focuses on harmonizing religious understanding, such as the interpretation of teachings, the implementation of worship, and the principle of inviting goodness to avoid evil, and informal communication that forms the Islamic identity of youth through social interaction, da'wah content, language style, peer influence, and elements of humor. This research contributes to opening new spaces for socio-religious studies that are more contextual and responsive to the social realities of contemporary Muslims.